Innovation and efficiency of food industry firms in Poland by regions - Zakrzewska, Aneta; Chojnacki, Piotr (Innowacyjność i efektywność przedsiębiorstw przemysłu spożywczego w Polsce w ujęciu regionalnym, 2019)
This paper was an attempt at assessing the innovation activity and efficiency of expenditure on innovation activity in food industry firms in Poland by regions and to identify the advantages of food industry firms from specific voivodeships in terms of their innovation activity and efficiency. Expenditure on and effects of the innovation activity in food industry firms in the respective voivodeships of Poland in 2016-2018 were analysed. As regards innovation, the most active units were those in the Mazowieckie and Małopolskie voivodeships. A strong propensity towards innovation and high efficiency were also noted in such firms in the Warmińsko-Mazurskie and Dolnośląskie voivodeships. The highest efficiency in the expenditure on innovation activity characterised the food industry in the Lubuskie and Opole voivodeships. Despite their strong propensity to innovate, the food industry firms in the Lublin and Mazowieckie voivodeships showed low efficiency, while those in the Łódź voivodeship performed the worst
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 7, s. 142-153
Keywords: innovation; efficiency; innovative firm; region; food industry; innowacyjność; efektywność; przedsiębiorstwo innowacyjne; przemysł spożywczy